Pelanggaran HAM di Kashmir sebagai Dampak dari Sengketa Wilayah India-Pakistan - Ines Florence Tabita Hutauruk; Mohamad Rosyidin; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Kashmir is one of the areas currently in dispute between India and Pakistan which is often accompanied by rebellions in which the people of Kashmir are victims. This conflict has caused human rights violations because many Kashmiris have been subjected to violence and restrictions on rights, especially women in Kashmir who are often victims of rape. The purpose of this study is to find out why the Kashmir conflict has resulted in a lot of sexual violence against women in Kashmir. This study was analyzed qualitatively using the literature method obtained from books, scientific articles, journals and mass media relevant to this topic. Furthermore, this research will be processed using a congruent method that focuses on cause and effect and is presented in an explanatory manner. Several previous studies have focused more on the territorial dispute between India and Pakistan and the interests of the two countries and less on the impact of these disputes on the Kashmiri community, especially women. So the novelty of this research is to complement another perspective in viewing the territorial dispute between India and Pakistan which previously did not highlight its impact on the enforcement of human rights in Kashmir, especially women because previous research focused more on the causes of the conflict. This research will be prepared using the concept of war crimes and the theory of using rape as a war strategy. The efforts of India and Pakistan in fighting over the Kashmir region often lead to violence in the local community. The main argument of this study is that the prevalence of sexual violence in the Kashmir region is influenced by the use of rape as a war strategy.